EFEKTIVITAS EDUKASI UNTUK MENINGKATKAN TINDAKAN MENCUCI TANGAN ANAK DI TK DARMA WANITA - Roza, Andalia; Nurhayati, Nurhayati (Ensiklopedia of Journal, 2024)
Hand washing is a process of mechanically collecting dirt and dust from the surface of the skin and reducing the number of microorganisms. The importance of hand washing education is to familiarize children with proper hand washing with soap and running water. The research objective was to determine the effectiveness of education to increase children's handwashing at Darma Wanita Kindergarten, Lipat Kain District, Kampar Regency, Riau Province in 2023. The research used was a quantitative method with a Quasi Experiment with control group research design. The population in this study were 30 kindergarten children at Darma Wanita Kindergarten, Lipat Kain District, Kampar Regency, Riau Province. The sample technique used is total sampling. The instrument used is the observation sheet. The results of research conducted at TK Darma Wanita showed that the distribution of respondents according to gender was a series with 15 women with 50% results and 15 men with 50% results. By age, the most was at the age of 5 years, amounting to 20 respondents (66.6%). Based on the table shows that of the 15 respondents in the pretest experimental group the highest number was in the implementation category which amounted to 8 respondents (52.7%). In the posttest experimental group, the highest number was in the implementation category, which amounted to 15 respondents (100%). Of the 15 respondents in the pretest control group, the highest number was in the non- executed category, amounting to 8 respondents (52.7%). Of the 15 respondents in the posttest control group, the highest number was in the implementation category, amounting to 15 respondents (100%). The results showed that the median before hand washing in the experimental group was 2,000 while the median after hand washing was 3,000 with P Value = 0,000 <α (0.001), and the median in the control group was 1,000 and after hand washing 3,000 with a P Value of 0.000. If seen from the posttest experimental group of 3,000 and the control posttest of 3,000 with a P Value of 0.180 <α (0.000) so that it can be concluded that the act of washing hands in children between the experimental and control groups after carrying out the action of washing hands there is a significant difference.Keywords: Education, the act of washing hands